Analisis Faktor-Faktor yang Mempengaruhi Prestasi Belajar Siswa Kelas 11 Rekayasa Perangkat Lunak pada Mata Pelajaran Basis Data di SMK National Media Center Malang - Panji Aris Setyawan; Satrio Hadi Wijoyo; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
SMK National Media Center Malang is a vocational school located in Malang City which has various majors, one of which is Software Engineering. Implementation of PLP at SMK National Media Center Malang that student achievement is generally in the form of grades accompanied by a minimum rating limit of 75. Assessment of student achievement in the form of knowledge competency can be carried out with written, oral tests, or assignments. The purpose of this observation is to analyze what factors influence student achievement in class 11 Software Engineering in the Database subject at SMK National Media Center Malang. To achieve this assessment, factors that play an important role are needed, including internal factors which have physical and psychological aspects, as well as external factors which have aspects of the family, school and community environment. The method used in this study was a quantitative type with 62 research subjects in class XI at SMK National Media Center Malang. The results of the research referring to percentage analysis show that all factors influence learning achievement. Percentage analysis shows a score on internal factors (physical) health aspect of 98.06%, disability 97.42%, intelligence 97.42%, attention 97.10%, interest 98.39%, talent 97.74%, motivation 98.65%, family environment 97.10%, school environment 98.71%, and community environment 96.45% where all of these aspects affect learning achievement based on percentage analysis.